Case report of hypercalcemia-related kidney complications after discontinuation of denosumab - van den Berg, Gerrit; Lilien, Marc R.; Knops, Rutger R. G.; van Es, Robert J. J.; van Dijk, Atty T. H.; Keijzer-Veen, Mandy G. (Frontiers in Pediatrics, 2025)
BackgroundThe use of the osteoclastogenesis inhibitor denosumab is increasing in pediatrics, especially in the treatment of giant cell tumor or granuloma of bone or jaw, aneurysmal bone cyst, and other rare bone disorders. Particularly in pediatric patients, adverse kidney effects—such as acute kidney injury (AKI), hypertension, and nephrocalcinosis—are a significant concern that has received little attention.Case-diagnosis/treatmentIn this report, we present three children who developed hypercalcemia-related AKI six months after discontinuation of denosumab treatment. Treatment of the hypercalcemia consisted of hyperhydration, and administration of furosemide, denosumab or bisphosphonate.ConclusionsClinicians should be aware of the side effects of denosumab for at least seven months after discontinuation of denosumab. Early diagnosis and prompt management of hypercalcemia will result in recovery of AKI, however long-term consequences cannot be ruled out.